Difference between revisions of "TADM2E 2.3"
(Recovering wiki) |
(No difference)
|
Revision as of 18:14, 11 September 2014
f(n) = (((n^2)(n+1)^2)/8) + n(n+1)(2n+1)/12
This problem does appear to break down into a series of nested summations:
<math> \displaystyle\sum_{i=1}^{n}\text{ } \displaystyle\sum_{j=1}^{i}\text{ } \displaystyle\sum_{k=j}^{i+j}\text{ } \displaystyle\sum_{l=1}^{j+i-k}1 </math>
In the last summation, the formula is independent of the iterator, which translates into adding the value 1, <math>j+i-k</math> times:
<math> \displaystyle\sum_{i=1}^{n} \displaystyle\sum_{j=1}^{i} \displaystyle\sum_{k=j}^{i+j}(j+i-k) </math>
Now the third summation goes from <math>j</math> to <math>i+j</math> the formula on closer examination reveals that
<math>\displaystyle\sum_{k=j}^{i+j}(j+i-k)</math> is <math> \displaystyle\sum_{k=1}^{i}(k) </math> which is equal to <math>i*(i+1)/2</math>
So the summation boils down to
<math> \displaystyle\sum_{i=1}^{n} \displaystyle\sum_{j=1}^{i} (i*(i+1)/2) </math>
The formula in the second summation is independent of the iterator, which translates to adding <math>i*(i+1)/2</math>, <math>i</math> times.
<math> \displaystyle\sum_{i=1}^{n}(i^2 * (i+1)/2) </math>
which is
<math> \displaystyle\sum_{i=1}^{n}((i^3 + i^2)/2) </math>
<math>\frac{1}{2} \left(\Sigma r^3 + \Sigma r^2\right) =
\frac{1}{2}\left(\frac{n^2\left(n+1\right)^2}{4} +
\frac {n \left(n+1\right)\left(2n+1\right)}{6}\right) =
\frac{n^2\left(n+1\right)^2}{8} + \frac {n \left(n+1\right)\left(2n+1\right)}{12}</math>
Time Complexity = O<math>({n}^{4})</math>